2015
DOI: 10.1111/sjos.12140
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Model Analysis of Partially Rank‐Ordered Set Samples: Age Groups of Fish from Length‐Frequency Data

Abstract: We present a novel methodology for estimating the parameters of a finite mixture model (FMM) based on partially rank-ordered set (PROS) sampling and use it in a fishery application. A PROS sampling design first selects a simple random sample of fish and creates partially rank-ordered judgement subsets by dividing units into subsets of prespecified sizes. The final measurements are then obtained from these partially ordered judgement subsets. The traditional expectation-maximization algorithm is not directly ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…However, one can easily see that LIJPScom1false(boldΨfalse|·false) still has a very complex form, due to the presence of functions of the following forms in f ( h : H ) (·; Ψ ), when h varies in {1,…, H }, f(·;Ψ)=j=1Mπjfj(·;bold-italicθj),F(·;Ψ)a=j=1MπjFj(·;bold-italicθj)aandF¯(·;Ψ)b=j=1MπjF¯j(·;bold-italicθj)b, with a , b ∈ {1,…, H }. To obtain an easier to use complete‐data likelihood function and proceed with a suitable EM algorithm, as described in the supplementary document, we define further latent vectors to obtain a new set of complete‐data denoted by bold-italicY=false{false(boldΔifalse[hfalse],bold-italicZifalse[hfalse],bold-italicWifalse[hfalse],bold-italicVifalse[hfalse]false),i=1,2,,n;h=1,,Hfalse} . The complete‐data likelihood function associated with Y is given below as the joint distribution of { X ∗ , Y } and will be used to estimate Ψ , …”
Section: Maximum Likelihood Estimation For Fmms Using Jps Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one can easily see that LIJPScom1false(boldΨfalse|·false) still has a very complex form, due to the presence of functions of the following forms in f ( h : H ) (·; Ψ ), when h varies in {1,…, H }, f(·;Ψ)=j=1Mπjfj(·;bold-italicθj),F(·;Ψ)a=j=1MπjFj(·;bold-italicθj)aandF¯(·;Ψ)b=j=1MπjF¯j(·;bold-italicθj)b, with a , b ∈ {1,…, H }. To obtain an easier to use complete‐data likelihood function and proceed with a suitable EM algorithm, as described in the supplementary document, we define further latent vectors to obtain a new set of complete‐data denoted by bold-italicY=false{false(boldΔifalse[hfalse],bold-italicZifalse[hfalse],bold-italicWifalse[hfalse],bold-italicVifalse[hfalse]false),i=1,2,,n;h=1,,Hfalse} . The complete‐data likelihood function associated with Y is given below as the joint distribution of { X ∗ , Y } and will be used to estimate Ψ , …”
Section: Maximum Likelihood Estimation For Fmms Using Jps Designmentioning
confidence: 99%
“…In the standard methods of modeling and inference for FMMs, samples are often obtained using the SRS design. Recently, finite mixture modeling based on other sampling designs such as RSS is considered in the literature and it is shown that RSS‐based estimators of FMM parameters are more efficient than their SRS counterparts . In spite of several successful applications of RSS, practitioners are still reluctant to use RSS in many practical problems, as they often prefer to have samples from the underlying population that can be used for multiple purposes.…”
Section: Introductionmentioning
confidence: 99%
“…These sampling designs are techniques to obtain more representative samples from the underlying population where measurement of the units is costly and/or time-consuming. In such sampling designs, sampling units are ordered fairly accurately by using available auxiliary information which may be costly to some extent (see [3]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of RSS, it has attracted significant attention from researchers and has generated both theory and methodology, as well as a wide range of applications in many different fields (e.g., Chen, Bai & Sinha, 2003;Wolfe, 2012, and references therein). Recent RSS development includes Frey, Ozturk & Deshpande (2007), Li & Balakrishnan (2008), Ghosh & Tiwari (2008), Ozturk (2013), Haq et al (2014), Ozturk & Jozani (2014), Hatefi, Jozani & Ziou (2014), Frey & Wang (2014), Hatefi, Jozani & Ozturk (2015), Ozturk (2015), Frey & Zhang (2017), , Zamanzade & Mahdizadeh (2018) and so on.…”
Section: Introductionmentioning
confidence: 99%